Molecular profiling of Chinese R‐CHOP treated DLBCL patients: Identifying a high‐risk subgroup. Issue 9 (5th June 2020) - Jiang, Shiyu; Qin, Yan; Jiang, Hongxin; Liu, Biao; Shi, Jianming; Meng, Fanlu; Liu, Peng; Yang, Jianliang; Yang, Sheng; He, Xiaohui; Zhou, Shengyu; Gui, Lin; et al.
Abstract: Diffuse large B‐cell lymphoma (DLBCL) is a clinically aggressive and heterogenous disease. Although most patients can be cured by immunochemotherapy, 30% to 40% patient will ultimately develop relapsed or refractory disease. Here, we investigated the molecular landscapes of patients with diverse responses to R‐CHOP. We performed capture‐based targeted sequencing on baseline samples of 105 DLBCL patients using a panel consisting of 112 lymphoma‐related genes. Subsequently, 81 treatment‐naïve patients with measurable disease and followed for over 1 year were included for survival analysis. Collectively, the most commonly seen mutations included IGH fusion (69%), PIM1 (33%), MYD88 (29%), BCL2 (29%), TP53 (29%), CD79B (25%) and KMT2D (24%). Patients with TP53 mutations were more likely to have primary refractory disease (87.0% vs 50.0%, P = .009). For those with TP53 disruptive mutations, 91.7% patients were in the primary refractory group. Interestingly, BCL‐2 somatic hypermutation was only seen in patients without primary refractory disease ( P = .014). In multivariate analysis, BCL‐2 amplification (hazard ratio [HR] = 2.94, P = .022), B2M mutation (HR = 2.99, P = .017) and TP53 mutation (HR = 3.19, P < .001) were independently associated with shorter time to progression (TTP). Furthermore, TP53 mutations was correlated with worse overall survival ( P = .049). Next, we investigated mutation landscape in patients with wild‐type (WT) TP5 3 (n = 58) and found that patients harboring MYD88 L265P had significantly inferior TTP than those with WT or non‐265P ( P = .046). Our study reveals the mutation spectrum of treatment‐naive Chinese DLBCL patients. It also confirms the clinical significance of TP53 mutations and indicates the prognostic value of MYD88 L265P in TP53 WT patients. Abstract : What's new? A significant percentage of diffuse large B‐cell lymphoma (DLBCL) patients will develop relapse or refractory disease from immunochemotherapy. In this study, the authors surveyed the molecular landscape of patients with diverse responses to the standard immunochemotherapy regimen, R‐CHOP. The findings demonstrated the clinical significance of TP53 mutation, BCL‐2 amplification, and B2M mutation. This study also revealed the prognostic potential of MYD88 L265P in wt TP53 patients, suggesting that the mutation could be used as a biomarker to stratify DLBCL patients. The new genomic framework contributes to elucidating the molecular attributes that may affect response to R‐CHOP treatment in DLBCL patients.